Forward-Backward Block-wise Channel Tracking in High-speed Underwater Acoustic Communication - Chen, Peng; Rong, Yue; Nordholm, Sven; He, Z. (IEEE, 2015)
Block-by-block decision-directed channel tracking is a bandwidth efficient channel estimation method for coherent underwater acoustic (UA) communication. However, conventional forward-only decision-directed method suffers from error propagation where the system bit-error-rate (BER) increases with theinterval between the pilot sequence and data symbols. To mitigate the error propagation effect, in this paper, a forward-backward decision-directed algorithm is proposed to detect data blocks which are at large internal from the previous pilot sequence but close to the next one. The proposed algorithm is applied to detect data received during the experiment conducted in December 2012 in the Indian Ocean off the Rottnest Island, Western Australia. The results show that using the proposed algorithm, the average uncoded BER of the last data block in one frame is much lower than the BER yielded by the forward-only tracking method and is only sightly higher than the BER of the first data block.